The International Database of Central Arterial Properties for Risk Stratification: Research Objectives and Baseline Characteristics of Participants - Aparicio, Lucas S; Huang, Qi-Fang; Melgarejo, Jesus D; Wei, Dong-Mei; Thijs, Lutgarde; Wei, Fang-Fei; Gilis-Malinowska, Natasza; Sheng, Chang-Sheng; Boggia, José; Niiranen, Teemu J; Odili, Augustine N; Stolarz-Skrzypek, Katarzyna; et al. (American journal of hypertension, 2022)
OBJECTIVE: To address to what extent central hemodynamic measurements, improve risk stratification, and determine outcome-based diagnostic thresholds, we constructed the International Database of Central Arterial Properties for Risk Stratification (IDCARS), allowing a participant-level meta-analysis. The purpose of this article was to describe the characteristics of IDCARS participants and to highlight research perspectives. METHODS: Longitudinal or cross-sectional cohort studies with central blood pressure measured with the SphygmoCor devices and software were included. RESULTS: The database included 10,930 subjects (54.8% women; median age 46.0 years) from 13 studies in Europe, Africa, Asia, and South America. The prevalence of office hypertension was 4,446 (40.1%), of which 2,713 (61.0%) were treated, and of diabetes mellitus was 629 (5.8%). The peripheral and central systolic/diastolic blood pressure averaged 129.5/78.7 mm Hg and 118.2/79.7 mm Hg, respectively. Mean aortic pulse wave velocity was 7.3 m per seconds. Among 6,871 participants enrolled in 9 longitudinal studies, the median follow-up was 4.2 years (5th-95th percentile interval, 1.3-12.2 years). During 38,957 person-years of follow-up, 339 participants experienced a composite cardiovascular event and 212 died, 67 of cardiovascular disease. CONCLUSIONS: IDCARS will provide a unique opportunity to investigate hypotheses on central hemodynamic measurements that could not reliably be studied in individual studies. The results of these analyses might inform guidelines and be of help to clinicians involved in the management of patients with suspected or established hypertension.
Keywords: hypertension; Cross-Sectional Studies; central blood pressure; Humans; blood pressure; kardiovaskulární nemoci; lidé středního věku; Middle Aged; Hypertension; Blood Pressure; Cardiovascular Diseases; mužské pohlaví; pulse wave velocity; průřezové studie; krevní tlak; Pulse Wave Analysis; pulse wave analysis; ženské pohlaví; hypertenze; analýza pulzové vlny; lidé; hemodynamics; cardiovascular outcome; Male; Female